Adobe - Givens, Michael (Sams, 2007)
With the release of the Apollo alpha, the code name of Adobe's new technology, the next generation of rich desktop applications is already under way. At an accelerating rate, new Apollo applications are vying for your PC's desktop real estate. Combining the existing web technologies you already know (Flex, AJAX, HTML, and others) with the Apollo runtime allows you to create engaging experiences for both Windows and Mac platforms that function even while disconnected from the network. In this Digital Short Cut, you will learn about the Apollo alpha and see a sample workflow for taking your current web development and server-side skills and applying them to create a new kind of desktop application. After reading this Short Cut, you will be well on your way to creating a different kind of desktop experience. Beginning with a sample application, Hello Apollo World, and progressing to a real-world desktop application, Go Fly, you will learn about some of the most important aspects of this exciting new technology. Apollo in Flight is targeted for developers that want just the facts - no fluff, only stuff.